The Effect of Applying Self- and Family-Oriented Written Education on the Management of Medicamentose, Clinical Exposure, and Quality of Life of Patient with Epilepsy - Kustiowati, Endang; Samsudi, Samsudi; Widodo, Joko; Kusumastuti, Kurnia (The Journal of Educational Development, 2018)
Epilepsy is a brain disorder characterized by a tendency to induce a continuous epileptic recurrence and neurobiological, cognitive, psychological, as well as social consequences. Epilepsy seizures are a series of signs and/or symptoms caused by abnormal neuronal activities in the brain. The purpose of this study was to prove the benefits of applying self- and family-oriented educational management to clinical outcomes, self-management, and impact of epilepsy on family, patient’s quality of life, family support, and the role of doctors and family of the epilepsy patient. This is an experimental research using two groups pre and posttest design. The subjects were 80 epilepsy patients ranging from 18 to 70 years of age. All subjects had never had any epilepsy surgery. The subjects were randomly assigned to treatment and control groups; 40 subjects in the treatment group received treatment and self- as well as family-oriented education while the other 40 subjects in the control group received treatment only. Family-oriented education was conducted using written materials on pathophysiology and epilepsy management, psychological effects of epilepsy, and information about the epilepsy community. All of the subjects answered the questionnaires prior to and 3 months after treatment. The questionnaires include information on seizure frequency and seizure-free status, medication adherence, self-management, epilepsy impact on patient and family, and quality of life. The results show that self- and family-oriented education can improve medication adherence, self-management, and family roles. Family-oriented education reduces the frequency of seizures as well as the impact of epilepsy on patients and families. It was concluded that self- and family-oriented education had a positive effect on medical management, clinical outcomes, self-management, and the quality of life of patients with epilepsy.